Strategic innovation and sustainability in Indonesia's oil and gas industry: a hybrid systematic literature review and bibliometric analysis - Tandiarak Agustinus; Purba John Tampil (Institute of Computer Science (IOCS), 2025)
This study explores how strategic innovation and sustainability converge in transforming Indonesia’s oil and gas sector amidst the global energy transition. Using a hybrid methodology (Systematic Literature Review and bibliometric analysis of Scopus-indexed articles from 2014-2025), it maps significant research clusters, key contributors and emerging themes. A marked increase in publications following Indonesia’s 2022 NDC update evidences growing alignment among dynamic capabilities, strategic innovation and sustainable practices (Cherepovitsyn & Rutenko, 2022; Nurhidayah et al., 2024). Yet, a persistent gap remains between corporate sustainability commitments and actual operational transformation. The paper’s contribution lies in integrating Dynamic Capabilities Theory, Strategic Innovation Theory and Sustainability Transitions Theory into a unified framework to support a just, innovative and sustainable energy future.